Formação de professores de matemática para o uso pedagógico de planilhas eletrônicas de cálculo: análise de um curso a distância via Internet. - Morgado, Maria José Lenharo (2003)
This study aimed at describing and analyzing the process of the formation of Mathematics teachers of the primary and secondary levels of education who participated of a distance learning course via Internet about the pedagogical use of calculus spreadsheets. The course was then elaborated, implemented and analyzed in its characteristics, which included the use of tools of the Web and of the calculus spreadsheet, as well as the interaction between teachers-students and the coordinator. The study also presented and analyzed the difficulties and facilities faced by participants in the development of the mathematical, pedagogical and computational contents that were part both of the activities proposed in the course modules and of the activities created by the participants themselves. Special attention was given to the evaluation of the methodological strategies employed by the coordinator so that teachers-students could acquire such types of knowledge. Questionnaires applied in the beginning and at the end of the course were used to identify categories of responses of teachers that indicated changes in their attitude related to teaching, learning and classroom practice issues. The study has a predominantly qualitative nature even though the numeric data give support to the analyses, which were based in multiple objective facts, in feelings demonstrated and reports given by the teachers. Among results, it should be highlighted the verification of a low level of communication with the coordinator. In addition, a gain of mathematical, pedagogical and computational knowledge was observed among the participants, with an emphasis on the pedagogical one, in sight that this was the most difficult and workful of all courses. According to the teachers, the interaction student-coordinator and student-materials contributed a lot to the gains just mentioned. It was observed that the active participation of the teachers in the distance course was strongly influenced by their experience with the use of computers, by the use of compatible and potent equipment both at home and at school. It was verified that the lack of time together with constant professional changes are the main factors interfering in teachers permanence and participation in distance courses. Finally, this study presents some recommendations about distance education in relation to the improvement of the Web environment as well as concerning the implementation of public policies related to the continued formation of teachers.